Ana María Barrenechea y su “circunstancia mexicana” - Rose Corral (Cuadernos LIRICO)
This paper seeks to document the importance of Ana María Barrenechea’s stay in the Colegio de México during 1954 and to analyse its consequences both on the personal level (in the Centre of Philological Studies between 1947 and 1953 she formed friendships with the group of Mexican and Latin American philologists who were formed by Raymundo Lida, a disciple of Amado Alonso) and on the academic and intellectual level (in Mexico she published the now classic study, La expresión de la irrealidad en la obra de Jorge Luis Borges, and several essays on Argentine literature). With her Argentinian colleague Emma Speratti Piñero, who spent a long period in the Colegio de México in the 1950s, she gave a series of talks on the fantastic literature of Argentina and she would never abandon this interest in the genre. Some of the many facets of Barrenechea’s relationship with Mexico can be reconstructed from the correspondence she exchanged with Julio Cortázar and with Alfonso Reyes, as well as from the letters that remain in the archives of the Nueva Revista de Filología Hispánica.